Goal Orientation and Academic Performance in Adult Distance Education - Neroni, Joyce; Meijs, Celeste; Leontjevas, Ruslan; Kirschner, Paul A.; De Groot, Renate H.M. (International Review of Research in Open and Distributed Learning, 2018)
Research has shown the importance of goal orientation in predicting academic performance for children, adolescents, and college students in traditional educational settings. Studies on this relationship within adult distance education, however, are lacking. To fill this gap, the present study was conducted to investigate the relationship between goal orientation and academic performance in adult distance learners. A sample of N = 1128 distance university students (age 18-75 years) filled out an online questionnaire. Their exam grades were collected from the files of the Open University of the Netherlands (OUNL). A mixed model regression showed performance approach goal orientation to be a positive predictor of academic performance, whereas performance avoidance and work avoidance were negative predictors of academic performance. Non-significant results were found for mastery approach as well as for mastery avoidance. Implications of these results are discussed.